Verbal Interactions of Peer Led Group Counselling - Guttman, Mary Alice Julius (Canadian Journal of Counselling and Psychotherapy, 2011)
Eight peer counsellors (four pairs of co-leaders) were randomly assigned to lead four counselling groups for the duration of eight sessions during a three-day retreat of an adolescent student organization. Peer counsellors differed as to their level of counsellor training. Four peers had received a year's training and practicum (high training) and four had received a minimum of training, consisting of three, four-hour workshops (minimally trained). An analysis of the verbal interactions of the sessions indicate no significant differences between the high and low training groups on the Hill Interaction Matrix HIM-G measures. The only exception was the members' ratio of the HIM. On this measure, more members of the low training groups made statements identifying themselves with their groups or the group process than members of the high training groups. Results are discussed in reference to implications for peer counsellor programs.